HUBUNGAN MAKP PRIMER MODIFIKASI DENGAN KEPUASAN KERJA PERAWAT RUMAH SAKIT PANTI NIRMALA MALANG - Maemunah, Neni; Sutriningsih, Ani; Rahayu, Tri Setiyo (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
The quality of nursing services as an indicator of the quality of health services is one of the determinants of Nursing as the largest number of professional groups. The Pirm Nirmala Hospital which was approved to apply the MAKP has been applied previously by the team method and since June 2018. The research objective is to study the relationship between the modification of the primary MAKP with the nurse's work leadership. The design of this study was cross sectional. The population was 183 nurses in the inpatient room by using a simple random sampling technique obtained a sample of 65 respondents with the inclusion criteria of implementing nurses, primary and associate. The statistical test results obtained from the primary MAKP with good categories were 52.31%, and nurse job satisfaction was 67.69% good categories. The value of the Spearman test for p value = 0,000, there is a relationship between the modification of the primary MAKP with nurse job satisfaction. The hospital is expected to improve the quality of the Primary MAKP modification and upgrade to the primary MAKP by further improving the quality of the nurse's HR and providing opportunities for all nurses to advance in education.